Deformations over non-commutative base - Kawamata, Yujiro (Comptes Rendus. Mathématique)
We make some remarks on deformation theory over non-commutative base. We describe the base algebra of semi-universal non-commutative deformations using vector spaces $T^1$ and $T^2$.